Kontribusi Penerapan Good Corporate Governance Dan Eco-Efficiency Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Pemoderasi - Bongsoikrama, Justin; Andini, Prita; Riyadi, Sugeng; Wulandari, Army Ardiani (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This research examines the value relevance of the concept of environmental efficiency which refers to the process of maximizing the effectiveness of business processes in order to minimize a company's environmental impact. This research aims to determine how the contribution of good corporate governance (GCG) and environmental efficiency is moderated by financial performance on company value. This research uses secondary data from 2018 to 2022 and was conducted on companies in the non-primary consumer goods industry sector listed on the Indonesia Stock Exchange. Information obtained from annual reports and sustainability reports. The sampling method used was the purposive sampling method, obtaining a sample of 56 companies with 280 observed data. This data analysis method uses Moderated Regression Analysis (MRA). The research results show that companies that implement eco-efficiency strategies can increase their company value. Eco-efficiency strategies are able to produce greater cost efficiency and profits, so they are carried out by companies to improve their financial performance. This research also found that financial performance was able to mediate the relationship between eco-efficiency and company value. However, this does not affect the ability to implement GCG to increase the company's performance value. The contribution of this research lies in analyzing the influence of eco-efficiency, GCG, on company value in customer goods companies with ISO 14001 Certificate.